Comparison of efficiency between risk malignancy index 1 and risk malignancy index 2 in diagnosing ovarian tumor - Budhathoki, Pawan; Shrestha, Prashant; Pradhan, Binita (Journal of Patan Academy of Health Sciences, 2025)
Introduction: The risk of malignancy index (RMI) is a validated clinical tool for stratifying risk of ovarian lesions. It is a scoring system based on menopausal status, ultrasound finding and CA-125 level. Various modifications have been made on scoring system to enhance its efficiency. The commonly used RMI is RMI 1 however recent studies suggest higher efficiency of RMI 2 over RMI 1. So, this study compares the efficiency of RMI 1 and RMI 2 on differentiating malignant ovarian tumor over benign one.Method: This analytical cross-sectional study done at Patan hospital included 172 women who underwent operation for ovarian tumor. Both RMI 1 and RMI 2 were calculated using Ultrasound score, CA-125 value and menopausal status and compared with histopathological diagnosis. The cut-off value was 200 for both RMI 1 and RMI 2 in discriminating malignancy. Chi square test and Receiver Operator Characteristics (ROC) curves were calculated.Result: Among 172 patients, 23 had malignant and 149 had benign ovarian tumor. The area under ROC curve for RMI 1 and RMI 2 was 0.973 and 0.969 respectively, which was statistically significant. The sensitivity and specificity of RMI 1 was 86.96% and 98.64%, whereas sensitivity and specificity of RMI 2 was 91.3% and 97.23% respectively. Similarly, positive predictive value (PPV) and negative predictive value (NPV) of RMI 1 was 90.9% and 97.98%, and that of RMI 2 was 84% and 88.63%, respectively.Conclusion: RMI 1 has higher specificity, PPV and NPV whereas RMI 2 has higher sensitivity in diagnosing ovarian tumor.